2017
DOI: 10.1111/1755-5922.12263
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of cardioprotective efficacy between fibroblast growth factor 21 and dipeptidyl peptidase‐4 inhibitor in prediabetic rats

Abstract: FGF21 exerts better metabolic regulation and inflammation reduction than vildagliptin. However, FGF21 and vildagliptin shared a similar efficacy for cardioprotection by improving HRV and LV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Long-term HFD intake in several strains of rat and mouse can cause hyperlipidaemia, peripheral insulin resistance, moderate hyperglycaemia and IGT, together with increase in the expression of inflammation and oxidative stress markers. 124,125 In rodents on HFD feeding, insulin resistance is followed by insufficient β-cell compensation, resulting in hyperinsulinaemia and altered glucose metabolism. 126 The effects of HFD depend not only on the source and percentage of calories but also on the animal species and strains used.…”
Section: Prediabetesmentioning
confidence: 99%
“…Long-term HFD intake in several strains of rat and mouse can cause hyperlipidaemia, peripheral insulin resistance, moderate hyperglycaemia and IGT, together with increase in the expression of inflammation and oxidative stress markers. 124,125 In rodents on HFD feeding, insulin resistance is followed by insufficient β-cell compensation, resulting in hyperinsulinaemia and altered glucose metabolism. 126 The effects of HFD depend not only on the source and percentage of calories but also on the animal species and strains used.…”
Section: Prediabetesmentioning
confidence: 99%
“…Regarding cell death, cardiac apoptosis has been reported in HFD-fed rats (Hsieh et al 2016, Tanajak et al 2017, Chen et al 2019, while the report on cardiac necroptosis following HFD consumption is limited (Giricz et al 2017). Necroptosis is initiated by inflammation (Dhuriya & Sharma 2018), as we showed that cardiac TNF-α protein levels were upregulated in our prediabetic rats.…”
Section: Discussionmentioning
confidence: 46%
“…Moreover, vildagliptin halted NLRP3 inflammasome activation and decreased IL-1β and IL-18 levels in free fatty acid-induced HUVECs [82].The anti-inflammatory properties of DPP-4i have been shown in different T1DM and T2DM animal models as well. Sitagliptin decreased serum levels of hs-CRP, IL-1β, MCP-1, and TNF-α in ZDF rats, while vildagliptin and linagliptin had a similar effect in high-fat diet-induced diabetic Wistar rats and western diet-induced diabetic C56Bl/6J mice [83][84][85]. In an STZ-induced T1DM diabetic Wistar rat model, sitagliptin also attenuated diabetic cardiomyopathy via the modulation of IL-6 levels and the JAK/STAT signaling pathway [86].…”
Section: Dpp-4imentioning
confidence: 92%